Byaṅ gter Spyan-ras-gzigs kyi sreg sbyaṅ lag len gsal bar bkod pa snaṅ byed ñi ma źes bya ba bźugs so - Padma-phrin-las, Rdo-rje-brag Rig-ʼdziṅ II, 1640?-1718 (s.n., 1970)
Funeral ritual from the Avalokiteshvara cycle of Changter (Byaṅ gter) rites of the Nyingmapa sect.